3D numerical study of heat and mass transfer of moving porous moist objects. (1st August 2021) - Çoban, Seda Özcan; Selimefendigil, Fatih; Öztop, Hakan F.
Highlights: 3D heat transfer and mass transfer from moving moist porous objects were analyzed. Increasing air temperature has an influence on increment of drying. Increasing air velocity also has an increasing effect on evaporation. Movement of the products can cause decrement on evaporation rate. Location and settlement of the product are important on conveyor belt dryers. Abstract: Heat and moisture transfer of two moving moist objects in a channel with convection of hot dry air is investigated numerically. A moving mesh approach is used for providing movement by means of the Arbitrary Lagrangian-Eulerian (ALE) framework. Governing equations for flow field and porous objects are solved by finite element discretization method for the 3D transient problem. Effects of drying air velocity and temperature are simulated by means of temperature, moisture content and heat transfer distributions. Results showed the importance of varying parameters on drying behavior. It was observed that the air velocity also has an increasing effect on evaporation and most reduction in moisture content is obtained at 0.8 m/s air velocity with 63.12% loss. Besides, there are insignificant differences between heat transfer values for fixed and moving objects, differences in average heat transfer values calculated between 6 and 13% for static bed and moving bed.